What is INCITEMI? Scientific and Technological Mining Institute - Instituto Científico y Tecnológico Minero - INCITEMI (1974)
The Scientific and Technological Mining Institute is a decentralized public organism under the Energy and Mines Sector, created by Decree Law N° 18880, General Mining Law, on June 8, 1971. As indicated by its name, its purpose is scientific and technological mining research, and the establishment of technical standards applicable to mining. By Decree Law NO 20237 dated December 4, 1973, its Organic Law was approved, according to which its organization and operation shall be governed. It is a juridical entity operating under interna/ public law, with administrative and economic autonomy, on a non-profit basis.